Analisis Persepsi Dosen terhadap Implementasi Perbankan Syariah dalam Kurikulum Pendidikan Tinggi (Studi Kasus Dosen Perbankan Syariah STAI Senori Tuban) - Mujib, Muhammad Abdul (Journal of Islamic Finance and Syariah Banking, 2024)
This research aims to explore the role of lecturers in developing the Sharia banking curriculum at STAI Senori Tuban, with a focus on the relevance and adaptability of the curriculum to industry needs. It is hoped that actively involving lecturers in the curriculum development process can improve the quality of education, prepare students to face challenges in the world of work and contribute to the growth of the sharia banking sector in Indonesia. Using a qualitative approach with a case study method, data was collected through interviews with 5 lecturers who taught Sharia banking courses. The research results show that although there is a positive perception of the curriculum, challenges such as a lack of references and training for lecturers still hinder teaching effectiveness. Lecturers also emphasized the importance of collaboration with industry to increase the relevance of the curriculum. This research recommends developing a curriculum responsive to industry changes and increasing lecturer involvement in the curriculum update process so that graduates can compete in an increasingly competitive job market. Thus, this research provides valuable insights for developing sharia banking in higher education in Indonesia.